Maternal Asian ethnicity and obstetric intrapartum intervention: a retrospective cohort study - Reddy, Maya (BMC Pregnancy Childbirth, 2017)
BACKGROUND: Maternal ethnicity is a recognized risk factor for stillbirth, such that South Asian women have higher rates than their Caucasian counterparts. However, whether maternal ethnicity is a risk factor for intrapartum outcomes is less clear. The aim of this study is to explore associations between maternal country of birth, operative vaginal delivery and emergency cesarean section, and to identify possible mechanisms underlying any such associations. METHODS: We performed a retrospective cohort study of singleton term births among South Asian, South East/East Asian and Australian/New Zealand born women at an Australian tertiary hospital in 2009–2013. The association between maternal country of birth, operative vaginal birth and emergency cesarean was assessed using multivariate logistic regression. RESULTS: Of the 31,932 births, 54% (17,149) were to Australian/New Zealand-born women, 25% (7874) to South Asian, and 22% (6879) to South East/East Asian born women. Compared to Australian/New Zealand women, South Asian and South East/East Asian women had an increased rate of both operative vaginal birth (OR 1.43 [1.30–1.57] and 1.22 [1.11–1.35] respectively, p < 0.001 for both) and emergency cesarean section (OR 1.67 [1.53–1.82] and 1.16 [1.04–1.26] respectively, p < 0.001 and p = 0.007 respectively). While prolonged labor was the predominant reason for cesarean section among Australian/New Zealand and South East/East Asian women, fetal compromise accounted for the majority of operative births in South Asian women. CONCLUSION: South Asian and South East/East Asian women experience higher rates of both operative vaginal birth and cesarean section in comparison to Australian/New Zealand women, independent of other risk factors for intrapartum interventions.